Does growth attract FDI? - Sasi Iamsiraroj; Hristos Doucouliagos (Kiel Institute for the World Economy (IfW), 2015)
FDI is seen widely as a vital source of investment, technology transfer, and growth. The factors that attract FDI have been a longstanding source of debate. The authors present a comprehensive assessment of the accumulated evidence on one factor, the success of economic growth in attracting FDI. Meta-regression analysis is applied to 946 estimates from 140 empirical studies. The authors show that there is a robust positive correlation between growth and FDI. Significantly larger correlations are established for single country case studies than with cross-country analysis. It also appears that growth is slightly more correlated with FDI in developing countries.
Keywords: O24; F21; 330; economic growth; FDI; meta-regression analysis